A Comparative Analysis between Maturity Models based on COBIT - Humberto Rocha de Almeida Neto; Edviges Mariza Campos de Magalhães; Alexandre J. H. de O. Luna; Hermano Perrelli de Moura; Leonardo A. V. de Souto; Victor Monteiro Silva (Anais do Encontro Anual de Tecnologia da Informação, 2012)
IT Governance gains prominence in respect to the competitiveness of business, establishing a set of mechanisms that allow the idealization of objectives, control formulas, metrics for implementation of strategies and evaluation of results from the Information Technology and Communication. COBIT (Control Objectives for Information and Related Technology) is one of the frameworks of "good practices" that implements these strategies into practice and it is used by various organizations for service management of Information Technology (IT) to assist the implementation of frameworks maturity models exist that aim to identify at what level the organization is a matter of maturity. This article is a comparative analysis between three of these maturity models based on the COBIT in order to provide relevant guidance and easy its deployment.